Tolerogenic Dendritic Cells Derived from Donors with Natural Rubber Latex Allergy Modulate Allergen-Specific T-Cell Responses and Ige Production - Acuna-Castillo, C (Public Library of Science, 2014)
Natural rubber latex (NRL; Hevea brasiliensis) allergy is an IgE-mediated reaction to latex proteins. When latex glove exposure is the main sensitizing agent, Hev b 5 is one of the major allergens. Dendritic cells (DC), the main antigen presenting cells, modulated with pharmacological agents can restore tolerance in several experimental models, including allergy. In the current study, we aimed to generate DC with tolerogenic properties from NRL-allergic patients and evaluate their ability to modulate allergen-specific T and B cell responses. Here we show that dexamethasone-treated DC (dxDC) differentiated into a subset of DC, characterized by low expression of MHC class II, CD40, CD80, CD86 and CD83 molecules. Compared with LPS-matured DC, dxDC secreted lower IL-12 and higher IL-10 after CD40L activation, and induced lower alloantigenic T cell proliferation. We also show that dxDC pulsed with the dominant Hev b 5 T-cell epitope peptide, Hev b 546â€"65 , inhibited both proliferation of Hev b 5-specific T-cell lines and the production of Hev b 5-specific IgE. Additionally, dxDC induced a subpopulation of IL-10-producing regulatory T cells that suppressed proliferation of Hev b 5-primed T cells. In conclusion, dxDC generated from NRL-allergic patients can modulate allergen-specific T-cell responses and IgE production, supporting their potential use in allergen-specific immunotherapy. © 2014 Escobar et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.